Principles of intraoperative neurophysiological monitoring and anaesthetic considerations. Issue 1 (January 2020) - Sanders, Brett; Catania, Santiago; Luoma, Astri MV.
Abstract: Surgery to the nervous system poses risks to neural structures be that mechanical, haemodynamical, chemical or thermal. The role of intraoperative neurophysiological monitoring (IONM) is to facilitate the assessment of the functional integrity of neural structures and provide a real time alerting system when changes caused by surgically induced insults are detected, with the goal of reducing the risk of postoperative neurological deficits. Furthermore, it is also used as a guidance system to map eloquent areas within the cortex and to identify specific neuronal structures, particularly when landmarks cannot be easily recognized. In this article, we focus on the various neurophysiological modalities used in intraoperative monitoring, their basic principles, indications and the information that they provide. We also examine the anaesthetic considerations and the checklist for the multidisciplinary team should an intraoperative alert be issued.